Price Flexibility and the Level of Income - Bergson, Abram (The Review of Economics and Statistics, 1943)
A it affects the community's propensities IV, to save and invest, so will a price-cut in any sector of the economy affect total real income. The observation is trite, but the systematic analysis of this interesting effect, in the light of recent devlopments in income theory, has not yet been undertaken. This essay, it is hoped, will provide the necessary tools for the project. The problem may be approached by considering an illuminating but probably quite unrealistic case. Suppose the producers of investment goods voluntarily reduce their prices, having been persuaded, (say) by reading the Brookings Institution study, Industrial Price Policies and Economic Progress,' that their profits ultimately will be enhanced thereby. That the producers might be disappointed the authors of the Brookings study themselves would grant the possibilityneed not for the moment concern us. What is of immediate interest is the community's gain. It is convenient and probably not remote from fact to assume that our enlightened producers execute their price reduction in a community in which the supply of money is highly elastic, and hence, in which interest rates do not change significantly under the impact of the events studied.2 Then the facts on which the impact of the price cut will depend can be discerned at once. Presumably, the reduction in prices will affect directly the demand for investment goods. That the effect will be positive, if interest rates are unchanged, is not implausible, but it suffices to observe here that unless the increase in demand is at least proportionate to the price cut, the money value of investment will be reduced. Subject to the same proviso, then, the community's investment activities will absorb less saving after the price cut than before, and saving will have to be curtailed. Apparently, unless the producers of consumption goods also are proselytized by the Brookings study, the price cut will have the paradoxical effect of reducing the community's real income. To suggest that if real income did increase, this in itself might induce an increased volume of investment is not in point. If the demand for investment were not stimulated sufficiently by the price cut alone, the increase in real income would not occur. The reduction in the price of investment goods, however, also affects at once the distribution of income. Even if the demand for investment goods did not respond at all to the price cut, could not the consequent reduction in entrepreneurial income cause the necessary reduction in saving? The answer, of course, is yesprovided that the producers of investment goods reduce their saving by the full amount of their loss. Even in this extreme although, perhaps in the shortest run, not unlikely case, however, both the community's money income and, if the price of consumption goods is unchanged, its real income are reduced. The burden is borne entirely by the adventurous, and not very abstemious, producers of investment goods. If the producers reduce their expenditures on consumption goods as well as their saving, the burden to that extent will be shifted to other members of the community. Provided the demand for investment goods responds at all to the price cut, employment, and hence the wage bill, as well as entrepreneurial income, will be altered. The question remains whether in this circumstance, at least, real income would not increase, even if the value of investment declined. The answer is neither unique nor simple. The impact of the price cut, of course, would depend on whether the change in total income as well as the change in its distribution resulted in a greater decline in the saving which the community desired to realize than in investment. Ultimately, however, real income would increase only if the 'Edwin G. Nourse and Horace B. Drury, Industrial Price Policies and Economic Progress (Brookings Institution, Washington, D. C., 1938). 2 The consideration of alternative banking policies is a task which it seems unwise to assume in this initial effort, but such a task should nrove laborious rather than difficiilt-